2021
DOI: 10.3390/biomedicines9060594
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell-Derived Exosomes Ameliorate Alzheimer’s Disease Pathology and Improve Cognitive Deficits

Abstract: The accumulation of extracellular β-amyloid (Aβ) plaques within the brain is unique to Alzheimer’s disease (AD) and thought to induce synaptic deficits and neuronal loss. Optimal therapies should tackle the core AD pathophysiology and prevent the decline in memory and cognitive functions. This study aimed to evaluate the therapeutic performance of mesenchymal stem cell-derived exosomes (MSC-exosomes), which are secreted membranous elements encapsulating a variety of MSC factors, on AD. A human neural cell cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 67 publications
2
68
0
Order By: Relevance
“…Chen et al, 2021 illustrated the curative mechanism of MSC-EXOs and proposed a cell-free MSC-EXO-based therapy method for treating AD. Results showed that the MSC-EXO therapeutic approach reduced Aβ expression, cleared brain glucose metabolism, and improved cognitive function and neuronal plasticity [ 55 ].…”
Section: Exosomes As a Drug Carriermentioning
confidence: 99%
“…Chen et al, 2021 illustrated the curative mechanism of MSC-EXOs and proposed a cell-free MSC-EXO-based therapy method for treating AD. Results showed that the MSC-EXO therapeutic approach reduced Aβ expression, cleared brain glucose metabolism, and improved cognitive function and neuronal plasticity [ 55 ].…”
Section: Exosomes As a Drug Carriermentioning
confidence: 99%
“…A study by Lu et al suggested stem cell implantation could reduce amyloid-β 40 and 42 accumulation by a clearance mechanism involving increased IDE and NEP levels [140]. A study by Chen et al showed stem cells prevented the downregulation of BDNF, which further supports the studies by Jones et al, Nakano et al, and Ager et al [138,139,143,162]. Neuronal memory and synaptic plasticity-related genes, such as BDNF, SYP, GluR2, and GRIN2B, have been shown to improve memory.…”
Section: Mechanisms Of Stem Cell Therapy In Admentioning
confidence: 70%
“…Coming full circle, recent studies have reestablished support for the previous view that stem cells can reduce both amyloid-β and tau levels, leading to enhanced cognitive function. Recent studies in the past 5 years from Chen et al, Li et al, Lee et al, McGinley et al, and Lu et al showed that MSC implantation could reduce levels of amyloid-β, leading to improved cognition in mice [ 131 , 138 , 140 , 142 ]. In addition to stem cells modulating BACE1 expression to alter APP processing, Lee et al also showed that stem cell transplantation could inhibit tau phosphorylation.…”
Section: Mechanisms Of Stem Cell Therapy In Admentioning
confidence: 99%
See 2 more Smart Citations